2013
DOI: 10.2172/1107470
|View full text |Cite
|
Sign up to set email alerts
|

Process Design and Economics for the Conversion of Lignocellulosic Biomass to Hydrocarbons: Dilute-Acid and Enzymatic Deconstruction of Biomass to Sugars and Biological Conversion of Sugars to Hydrocarbons

Abstract: The U.S. Department of Energy (DOE) promotes the production of a range of liquid fuels and fuel blendstocks from lignocellulosic biomass feedstocks by funding fundamental and applied research that advances the state of technology in biomass collection, conversion, and sustainability. As part of its involvement in this program, the National Renewable Energy Laboratory (NREL) investigates the conceptual production economics of these fuels.Between 1999 and 2012, NREL conducted a campaign to quantify the economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
578
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(584 citation statements)
references
References 78 publications
4
578
1
1
Order By: Relevance
“…In fact, overall economics of bio-ethanol production depend heavily on the cost of the feedstock (Davis et al, 2015). Thus, economically viable production of bioethanol requires careful process logistics and supply-chain consideration.…”
Section: Biomassmentioning
confidence: 99%
“…In fact, overall economics of bio-ethanol production depend heavily on the cost of the feedstock (Davis et al, 2015). Thus, economically viable production of bioethanol requires careful process logistics and supply-chain consideration.…”
Section: Biomassmentioning
confidence: 99%
“…Decreasing ash can lead to more effective dilute acid pretreatment, because ash can neutralize the acid, and reducing extractives typically increases enzymatic activity. Air classification boosted the hybrid poplar total sugar content above 59%, which is generally agreed upon as suitable for biochemical conversion (Davis et al, 2013). Additional compositional analysis data can be found in the supporting information for these same samples.…”
Section: Biochemical Conversion With Air Classificationmentioning
confidence: 53%
“…A comprehensive 2013 report by the US National Renewable Energy Laboratory (NREL) concluded that achievement of the target value of 3.00 US dollars per gallon of gasoline equivalent fuel required lignin valorization [242]. Kautto et al modeled the organsolv-based production of ethanol from hardwood with lignin, furfural, and acetic acid as co-products [243].…”
Section: Economic Analysis Of Lignin Utilization Strategiesmentioning
confidence: 99%